Antecedent factors and consequences of job satisfaction in the Jordanian hotel industry - Alown, Bandar Ersan
Worldwide, the hospitality industry has been growing and it is highly a competitive sector. It is also considered as one of the major sectors in the Jordanian economy. The hotel industry is service-oriented involves people in delivering the services. In this context, satisfied employees delivering high service job performance meeting customers' expectation is crucial in the hotel sector to remain competitive. However, there is a decline in job performance among Jordanian hotel employees. Literatures suggested that leadership style, organisation structure, job satisfaction and quality of work would improve employees' job performance.The objectives of the study are; first, to examine the effect of organisational structure and leadership style on employees' job satisfaction; second, to examine the effect of employees' job satisfaction on job performance; third, to examine the effect of employees' job satisfaction on quality of work-life; fourth, to examine the quality of work-life on job performance, fifth, to determines the mediating role of quality of work-life on the relationship between employees' job satisfaction and job performance. This study applied a causal research design to explain the causal relationships that exist among the study variables. A total of 430 front-line Jordanian employees working in the Jordanian hotel industry were selected to participate in the study. Respondents were selected using a two-step sampling technique; area sampling and simple random sampling technique. Selfadministered questionnaires were distributed to the respondents after pre-test and pilot test were conducted. Data analysis was performed using the Statistical Package for Social Science Program (SPSS) software version 21. Structural Equation Model (SEM) using the IBM SPSS AMOS 21.0 was applied to the dataset to test the proposed hypotheses. The study discovered a moderate level of job performance, quality of worklife, job satisfaction and organisational structure among the respondents. However, the study revealed a high level of organisations leadership style. The findings of the study supported all the proposed hypotheses. The organisational structure has a positive significant effect onjob satisfaction; leadership style has a significant positive effect on job satisfaction; job satisfaction has a significant positive effect on job performance, and quality of work-life has a significant positive effect on job performance. The mediation analysis illustrated that the quality of work-life had a partial mediation effect on job satisfaction and job performance relationship. The findings of this study contributed to theoretical and practical implications. The development of a good organisational structure and leadership style within the hotel industry in Jordan would assist in providing a high job satisfaction among the employees. High job satisfaction leads to high job performance. Quality of work-life is also a crucial factor to improve job performance. Future research should include other variables such as organisational culture, emotional intelligence and organisational commitment which, probably could explain more about the variance in problem behaviour.